UJI EFEKTIVITAS INFUSA DAUN BINAHONG (ANREDERA CORDIFOLIA) TERHADAP PROFIL LIPID TIKUS HIPERLIPIDEMIA: EFFECTIVENESS TEST OF BINAHONG LEAF INFUSION (ANREDERA CORDIFOLIA) ON LIPID PROFILE OF HYPERLIPIDEMIA RATS - Sari, Novita; Anasis, Annisa Mulia; Nurjanah, Siti; Mulyani, Yuli Wahyu Tri; Hidayasari, Nur Wafa; Romadhani, Sucitra Anugerah; Kristiana, Mita (JFL : Jurnal Farmasi Lampung, 2025)
Hyperlipidemia is a lipid disorder characterized by increased levels of total cholesterol, triglycerides, LDL or decreased HDL in the blood. A High lipid level is a strong marker of the risk factors for cardiovascular diseases. The research aims to identifity Effect of Binahong leaf infusion (Anredera cordifolia) on Lipid Profile in Hyperlipidemia Rats. Experimental study of pretest-posttest control group design. Rats were given a high-fat diet (HFD) and Propylthiouracil (PTU) 1% for 21 days. After hyperlipidemia archieved, rats were divided randomly into five groups: negative control, positive control, treatment groups with Binahong leaf infusion (Anredera cordifolia) 100, 200 and 300 mg/200BW/day. Blood was taken for lipid profile measurements in hyperlipidemia conditions and after treatment with Binahong leaf infusion (Anredera cordifolia) for 14 days. The statistical analysis that had been done used ANOVA with an LSD test. The result showed that giving of Binahong leaf infusion (Anredera cordifolia) 100, 200 and 300 mg/200BW/day in hyperlipidemia rats reducted of total cholesterol, triglycerides, LDL and increased HDL levels significantly (p<0,05) than negative control but less effective compared to positive control. Binahong leaf infusion (Anredera cordifolia) has been shown to effectively reducted of total cholesterol, triglycerides, LDL and increased HDL levels in hyperlipidemia rats. Keywords: Anredera cordifolia, binahong, cholesterol, infuse, lipid profile